2014
DOI: 10.4028/www.scientific.net/kem.608.103
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Rice Husk Ash and Waste Sludge from Cutting Glass Manufacturing with Angthong Pottery

Abstract: Efficiently utilization of rice husk ash (RHA) and waste sludge from cutting glass manufacturer (WSG) as additives to pottery clay would yield positive economic impacts, such as more friendly industrial ecosystems. In this study, The RHA and WSH were used as additives to Angthong pottery clay (APC) and casting and fired properties were examined. Two sets of sample with a mixture consisting of 60% APC, 20% RHA, and 20% WSG (CRG formula) and non-added clay (C100 formula) were prepared by slip casting technique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In general, the community industries in Angthong province have been using these local clays to produce tiles, bricks, pottery, etc. However, utilizing the depleting natural resources for a long time, Angthong clay in Thailand has decreased in recent years [4]. Therefore, finding a solution for such resource scarcity is urgent matter and it can be done by exploit alternative materials from the waste industry as an effective way to achieve Angthong clay sustainability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the community industries in Angthong province have been using these local clays to produce tiles, bricks, pottery, etc. However, utilizing the depleting natural resources for a long time, Angthong clay in Thailand has decreased in recent years [4]. Therefore, finding a solution for such resource scarcity is urgent matter and it can be done by exploit alternative materials from the waste industry as an effective way to achieve Angthong clay sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous research, Kaewtabut et al reported similar study utilized 60% Angthong clay, 20% RHA, and 20% waste sludge from the cutting glass and compared with the 100% clay fired at 900°C. Therefore, the results showed low shrinkage led to high water absorption, but did not affect the mechanical strength [4]. Wangrakdiskul et al developed greyish colored wall tiles by utilizing 10% RHA, 60% green glass cullet, and 30% white clay.…”
Section: Introductionmentioning
confidence: 99%